Long-Term Consequences of Childhood Maltreatment Among Postpartum Women—Prevalence of Psychosocial Risk Factors for Child Welfare: An Independent Replication Study - Hitzler, Melissa; Bach, Alexandra M.; Köhler-Dauner, Franziska; Gündel, Harald; Kolassa, Iris-Tatjana (Frontiers in Psychiatry, 2022)
As an especially burdensome experience, childhood maltreatment (CM) can have long-lasting consequences on wellbeing and mental health well into adulthood. We have previously reported that CM constitutes a central risk factor not only for the development of mental problems, but also for facing additional psychosocial risks, endangering healthy development of mother and offspring throughout life (e.g., financial problems, intimate partner violence, substance use). This study was designed to replicate these findings in a larger, independent study cohort. In this cross-sectional replication study an independent cohort of 533 healthy postpartum women were interviewed within seven days after parturition. CM experiences were assessed retrospectively using the German version of the Childhood Trauma Questionnaire (CTQ) and current psychosocial risk factors for child welfare were assessed using the Konstanzer Index (KINDEX). Of all women, 16.1% experienced emotional and 10.1% physical abuse, 28.5% emotional neglect, 9.4% physical neglect and 10.3% experienced sexual abuse. Most importantly, the higher the CM load the more psychosocial stressors existed in women’s life. Particularly, women with higher CM load had a higher risk for mental health problems, intimate partner violence, financial problems, and a higher postnatal stress load. In an independent sample, this study replicated the previous findings that CM and psychosocial risk factors for child welfare were strongly associated in a dose-response manner. Our results emphasize the higher vulnerability of women with a CM history in the postpartum period. To avoid negative consequences for mother and child, a regular and evidence-based screening for CM and psychosocial risk factors during pregnancy and puerperium is needed to identify at-risk mothers early during pregnancy and to provide appropriate support. Hence, our findings highlight the mandatory requirement for an interdisciplinary collaboration of gynecological practices, hospitals and midwifes, along with psychologists and psychotherapists and child and youth welfare services.